On the Optimal Reform of Income Support for Single Parents - Salvador Ortigueira; Nawid Siassi (TU Wien, Institute of Statistics and Mathematical Methods in Economics, Research Unit in Economics, 2021)
We characterize the optimal reform of U.S. income support for low-income single parents. We develop a heterogeneous agents model with idiosyncratic risk and incomplete asset markets where single parents evolve through three life stages defined by their children's care needs. Using the U.S. tax-transfer system as the benchmark policy and a sample of single mothers drawn from the CPS, we assess reforms that maximize the expected utility of entering mothers. When policy cannot be tagged by the single mothers' life stage, the optimal reform calls for an increase in out-of-work income support by 11 percent, from 6,320 to 7,080, and a decrease in the wage subsidy to low-wage workers from 34 to 22 percent. This reform delivers substantial welfare gains for single mothers-to-be, and has the support of a vast majority of incumbent mothers. Tagging policy by the life stage makes the government's trade-off between providing insurance to single mothers in stage one (child in pre-schooling age) and incentivizing them to work when they transit to stage two (child in school age) more favorable, thus increasing their scope for smoothing marginal utility throughout life stages. Single mothers in stage one receive 8,950 in out-of-work support, and no subsidies to low-wages. For single mothers in stage two the optimal reform prescribes a reduction in out-of-work income support and an increase in work subsidies. Tagging brings additional welfare gains.
Keywords: D15; E21; E61; 330; Optimal income transfers; Single-parent households; Intertemporal savings and labor supply